Twitter (X), Investor Sentiment, and Market Inefficiency: A Case Study of Indonesia - Dewi, Ratna Arista (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study examines the impact of Twitter (X) sentiment on market inefficiency (proxied by stock mispricing) in Indonesia, based on an analysis of 600 observations. Stock mispricing, which arises due to inefficiencies in the capital market, is significantly influenced by investor sentiment. With the growing role of technology, social media platforms, particularly Twitter (X), have become valuable tools for measuring market sentiment. Using the Vector Autoregressive (VAR) model, our findings indicate that Indonesian stock prices in were undervalued by 19.5%, and Twitter sentiment had a significant negative effect on stock mispricing, suggesting that pessimistic sentiment can lead to deviations from fundamental stock values. These findings reinforce the behavioral finance perspective, which argues that investor emotions influence market movements beyond traditional financial indicators. The study also emphasizes the need for investors to consider both market fundamentals and sentiment trends on social media before making investment decisions. Given the growing role of digital platforms in shaping financial perceptions, understanding investor sentiment on Twitter can provide valuable insights for market participants.